АЛИШЕР НАЎАЙЫНЫӉ ДӨРЕТИЎШИЛИГИ ҲӘМ ТҮРКМЕН ӘДЕБИЯТЫ - Керуенов, Т. (ILIM hám JÁMIYET, 2023)
This article describes the role of Alisher Navoi’s works, the Uzbek classic poet of the 15th century, in Turkmen literature and considers a comparative analysis of the issues of the literary influence of Alisher Navoi’s literary heritage on the work of Maktimkuli. The role of Navoi and Maktimkuli’s works in friendly relationships between the Uzbek-Turkmen peoples is also discussed.